MAKNA BELAJAR BAGI PESERTA DIDIK PROGRAM MANDIRI PAKET C DI HOMESCHOOLING (Studi Fenomenologi di Homeschooling Bandung) - Utami, Puji Ratna Dwi; Handayani, Sri; Wasliman, Eva Dianawati (Universitas Negeri Jakarta, 2025)
Education is a process of interpreting experience that plays an essential role in developing individuals’ potential, skills, and character. The Independent Paket C Program at Homeschooling Focus serves as a non-formal education alternative that emphasizes flexibility, personalized learning, and a learner-centered approach. This study aims to explore the meaning of learning as experienced by learners in the Independent Paket C Program using a phenomenological approach. This research addresses a gap in phenomenological studies on the independent Paket C program, which has been less explored compared to homeschooling in general. The findings contribute to improving the management of non-formal education and encourage flexibility-oriented policies in homeschooling. This study employed a phenomenological qualitative research design involving active learners, alumni, tutors, and the school principal as participants. Data were collected through non-participant observation, semi-structured interviews, and document analysis. Data analysis followed phenomenological stages, including horizontalization, thematic clustering, the development of textual and structural descriptions, and the formulation of the essence of learning experiences. Data trustworthiness was ensured through source and method triangulation, member checking, peer debriefing, and audit trails. The findings indicate that learners perceive learning as a process of self-development, goal attainment, character formation, and a meaningful and enjoyable learning experience. Flexibility in learning time, methods, and objectives, supported by supportive tutor–learner relationships and a psychologically safe learning environment, plays a significant role in shaping learners’ perceptions of learning. Furthermore, the study reveals positive attitudinal changes among learners, who developed from passive and less confident individuals into more independent, responsible, and intrinsically motivated learners. In conclusion, the Independent Paket C Program facilitates a humanistic, holistic, and adaptive learning process. Keywords: The Meaning of Learning, Paket C Program, Homeschooling, Independent Program, Phenomenology.